Transition phase of nutrition—optimizing nutrient administration - Alur, Pradeep; Ramarao, Sumana (Frontiers in Pediatrics, 2025)
This discussion explores the complex aspects of managing nutrition for preterm infants during the critical transition from exclusive parenteral nutrition (PN) to full enteral feeding (EN). The primary objectives of nutritional care in this very low birth weight infants (VLBW) population are to promote growth rates comparable to those in utero and enhance key neurodevelopmental milestones. The transition phase is characterized by the gradual increase of enteral feeds concurrently with the reduction and eventual cessation of parenteral nutrition. This period presents several key challenges in clinical practice, marked by notable variability: (A) determining the appropriate timing and criteria for initiating enteral feeds; (B) optimizing the rate at which enteral feed volumes are safely increased; (C) deciding the specific enteral volume threshold when to initiate human milk fortification to meet increasing caloric and protein demands; (D) establishing the optimal timing for discontinuing intravenous lipid emulsions (ILE); and (E) identifying the precise enteral volume threshold that dictates when to cease parenteral amino acid administration. To navigate these complexities and ensure seamless nutrient administration, practical recommendations for effective management are crucial. These include advocating for early fortification of human milk, judicious use of concentrated parenteral nutrition to provide adequate nutrients in lower fluid volumes, and strategically minimizing the overall duration of the transition phase. Implementing these evidence-informed steps aims to ensure smooth nutrition management, optimize nutrient delivery, and significantly reduce the pervasive risk of postnatal growth failure in extremely low birth weight infants.